Evolution of terrestrial herbivory: nutrient stoichiometry, body size, and dietary diversity - Boyce, C. Kevin (Frontiers in Ecology and Evolution, 2023)
Direct fossil preservation of leaf damage, arthropod mouthparts, and vertebrate teeth has understandably led to a focus on oral processing of plant material when considering the evolution of herbivory in deep time. Here, nutrient stoichiometry is advocated as an important alternative constraint on the evolution of herbivory. Most life possesses C:N ratios of approximately 7:1, but uniquely among land plants that ratio can be skewed to 1000:1 in some tissues due to the abundance of cell wall structural polymers that lack nitrogen entirely. Since the superabundance of carbon is unevenly distributed between and within plant organs and tissues, avoidance is a viable strategy for herbivores, but availability is dependent upon herbivore body size. Sub-millimeter herbivores can attack plants cell-by-cell, avoiding cell wall consumption entirely in favor of cell contents, thereby presenting little stoichiometric distinction between herbivory and consumption of animals, fungi, or unicellular life. Insect-sized herbivory at least allows avoidance of the most carbon-rich/nutrient-poor tissues within a plant organ. However, vertebrate sizes prevent such selectivity. The increasing challenges of nutrient stoichiometry with increasing herbivore body size is recapitulated through time in the fossil record. The first herbivores were microherbivores that can avoid cell wall consumption-present already with their first opportunity for fossil preservation in the Early Devonian. Tissue-specific consumption by insect herbivores followed in the Carboniferous. 150 million years would pass after the first microherbivory record before vertebrate herbivory would reach its modern prevalence.